ASPECTS OF ENTERPRISE INNOVATIVE DEVELOPMENT IN THE CONTEXT OF DOMESTIC MARKET DEVELOPMENT ON AN INNOVATION BASIS (Development Service Industry Management, 2025)
The study analyzes methodological and applied provisions for the development of agricultural enterprises and the agricultural products market of Ukraine on an innovation basis. The purpose of the article is defined as the generalization of existing and the substantiation of new aspects of innovative enterprise development in the context of domestic market development on an innovation basis. The article examines the significance of innovations as one of the leading factors in ensuring the competitiveness of enterprises, sectors, and strategically important branches of the national economy of Ukraine. Particular attention is given to the agricultural sector, which plays a key role in strengthening the economic and food security of the state, as well as in shaping its export potential. It is noted that the current state of innovative activity of domestic agricultural enterprises remains low, which is manifested in the insufficient level of implementation of digital technologies, biotechnologies, precision farming tools, and other innovative solutions. This, in turn, reduces their competitiveness both in the domestic and foreign markets. The necessity of forming and implementing effective managerial decisions aimed at the innovative development of agricultural enterprises and the agricultural products market of Ukraine is substantiated. A set of state regulation measures is proposed, including: stimulation of investments in the field of agricultural innovations, improvement of the system of tax and financial incentives for innovative enterprises, development of agricultural clusters and innovation hubs, as well as expansion of cooperation between business, research institutions, and state structures. The implementation of these measures will increase the efficiency of the agricultural sector, strengthen its competitive positions, and contribute to raising the level of economic security of Ukraine.
Keywords: agricultural products market; agricultural enterprises; innovations; innovation activity; innovative activity; innovative development; state policy; domestic market; innovation basis